2022
DOI: 10.1038/s41598-022-05209-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of adjuvant trastuzumab in women with HER2-positive T1a or bN0M0 breast cancer: a population-based cohort study

Abstract: Adjuvant trastuzumab has been associated with superior survival in women with ≥ T1c or node-positive HER2-positive early-stage breast cancer; however, there is a lack of phase III trials in women with T1a/bN0 disease. Our study aimed to assess the outcomes of women with HER2-positive T1a/bN0 breast cancer who received adjuvant trastuzumab in Saskatchewan, Canada. We evaluated all women diagnosed with HER2-positive T1a/bN0 breast cancer in Saskatchewan between 2008 and 2017. We performed Cox proportional multiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Even back 35 years ago, the prognostic value of HER2 was reported greater than that of HRs [38]. However, the use of trastuzumab in patients overexpressing HER2 showed that those patients could be managed by reducing the risk breast cancer recurrence [39], supporting the importance of this test in breast cancer patients [10,40].…”
Section: Discussionmentioning
confidence: 99%
“…Even back 35 years ago, the prognostic value of HER2 was reported greater than that of HRs [38]. However, the use of trastuzumab in patients overexpressing HER2 showed that those patients could be managed by reducing the risk breast cancer recurrence [39], supporting the importance of this test in breast cancer patients [10,40].…”
Section: Discussionmentioning
confidence: 99%
“…Even back 35 years ago, the prognostic value of HER2 was reported greater than that of HRs [35]. However, the use of trastuzumab in patients overexpressing HER2 showed that those patients could be managed by reducing the risk breast cancer recurrence [36], supporting the importance of this test in breast cancer patients [9,37]. Unfortunately, this targeted therapy not currently used in Rwanda.…”
Section: Discussionmentioning
confidence: 99%
“…A study using the National Cancer Database reported that adjuvant chemotherapy was associated with an improved 5-years OS (96.8 vs. 92.3%) in patients with T1bN0M0 breast cancer, while no benefit was observed in patients with T1aN0M0 and T1miN0M0 breast cancer ( 22 ). However, another retrospective non-randomized study reported that anti-HER-2 therapy may benefit patients with pT1a/bN0M0 HER-2-positive malignant breast tumors ( 13 ). However, patients with T1a and T1b disease were not analyzed separately in the aforementioned study.…”
Section: Discussionmentioning
confidence: 99%